2015
DOI: 10.1142/s0218810415500033
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation, Validation, and Reliability of the Michigan Hand Outcomes Questionnaire Among Persian Population

Abstract: We aimed to validate a cross-culturally adapted version of the Persian Michigan Hand Outcomes Questionnaire (MHOQ). We followed the Beaton's guideline to translate the questionnaire to Persian. We administered the final version to 223 patients among which 79 patients returned 3 days later to respond to the Persian MHOQ for the second time. In the first visit, respondents also filled the Disabilities of the Arm Shoulder and Hand (DASH) and rated the pain based on the Visual Analogue Scale (VAS). Cronbach's alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
3
10
1
Order By: Relevance
“…The ICC of the total score of the MHQ-Thai version showed excellent test-retest reliability for patients with hand injuries. The ICC for each domain was also good to excellent, which was a similar result to the original MHQ and the other translated MHQs [5, 16, 18, 19, 21, 22]. This indicated that the domains in the MHQ-Thai version were highly reliable in repeated testing and were stable over time.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The ICC of the total score of the MHQ-Thai version showed excellent test-retest reliability for patients with hand injuries. The ICC for each domain was also good to excellent, which was a similar result to the original MHQ and the other translated MHQs [5, 16, 18, 19, 21, 22]. This indicated that the domains in the MHQ-Thai version were highly reliable in repeated testing and were stable over time.…”
Section: Discussionsupporting
confidence: 71%
“…An instrument achieves reliability if it produces consistent, reproducible results on repeated administration [17]. The MHQ-Thai version revealed high internal consistency, which was in line with the original MHQ and the MHQs in other languages [5, 16, 18, 19]. Various translations still retained similarly high Cronbach's alpha coefficient even after cross-cultural adaptation.…”
Section: Discussionmentioning
confidence: 56%
“…This implies that measurements of capacity such as grip and key pinch forces only partially reflect the disability patients suffer, as the maximal capacity is rarely needed in normal daily activities. Compared with other language versions of the MHQ, the correlations we found were slightly stronger (10)(11)(12)(13)(14). Four MHQ subscales had a strong correlation with the DASH score, with the ADls subscale having the strongest correlation.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, this tool has been proven to be valid and has demonstrated a high standardized response mean (SRM) in many types of hand/wrist injuries and disorders [10,14,[18][19][20][21][22]. The MHQ has been translated and cross-culturally adapted into many languages including Turkish [23], Brazilian [24], Korean [25], Japanese [26], German [27], Persian [28], Polish [29], French [30], Finnish [31] and Thai [32].…”
Section: Introductionmentioning
confidence: 99%